An IS26 variant with enhanced activity. Issue 3 (7th February 2019) - Pong, Carol H; Harmer, Christopher J; Ataide, Sandro F; Hall, Ruth M
ABSTRACT: The insertion sequence IS 26 plays a major role in the mobilization, expression and dissemination of antibiotic resistance genes in Gram-negative bacteria. Though IS 26 is abundant in sequenced genomes and in plasmids that harbour antibiotic resistance genes, only a few minor variations in the IS 26 sequence have been recorded. The most common variant, IS 26 * (also known as IS 15 Δ1), encodes a Tnp26 transposase with a single amino acid substitution, G184N in the catalytic domain. Using computational modelling, this substitution was predicted to increase the length of the helix that includes the E173 residue of the catalytic DDE triad, and its effect on activity was tested. An IS 26 mutant generated in vitro producing Tnp26-G184N formed cointegrates in a standard untargeted reaction at 5-fold higher frequency than IS 26 producing Tnp26. When the target included a single copy of IS 26, the G184N substitution increased the cointegration frequency 10-fold and the reaction was targeted and conservative. Hence, the substitution increased Tnp26 activity. The longer helix may stabilise the position of the E173 of the DDE for the catalysis reaction and the specific G184N substitution may also enhance activity by increasing binding to the terminal inverted repeats. Abstract : IS26 is one of the major players moving antibiotic resistance genes in Gram-negative bacteria, and an IS26 variant has been shown to have increased activity.